The Effect of Whatsapp in A Flipped Classroom on Students’ Writing Achievement at MTsN 1 Konawe - Tarisman,; Hanafi, Hilaluddin (Advances in Social Sciences Research Journal, 2020)
This study aims at finding out the significant effect of using WhatsApp as a media in a flipped classroom on students’ writing achievement. This study applied the pre-experimental design. The population was the 2017/2018 second grade students of MTsN 1 Konawe which consists of 240 students. The samples were 30 students of Class VIII-2. The experimental class was taught by using WhatsApp Group chat as a flipped classroom media. The tests consisted of pre-test and post- test. The instrument used in this study was a writing test. The data were analyzed by using paired sample t-test. The hyphotesis of this research stated if there was a significant effect of using WhatsApp on students’ writing achievement at MTsN 1 Konawe (H1). The result of paired sample t-test shown that the asymp sig. is 0.000. It means that the asymp sig. was lower than 0.05 (0.000 < 0.05). Therefore, the H1 is accepted. It can be concluded that WhatsApp has significant effect on students’ writing achievement at the second grade students of MTsN 1 Konawe..